Dose Analysis of Prostate Cancer Therapy with X-Ray Therapy using PHITS Program Version 3.341 - Febriansyah, Tri Nanda; Pratiwi, Beta Nur; Pramono, Subur; Sardjono, Yohannes; Triatmoko, Isman Mulyadi; Wijaya, Gede Sutrisna; Prasetio, Heru; Hidayati, Nur Rahmah; Nuraeni, Nunung; Ulya, Syarifatul; et al. (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2026)
According to statistics from the WHO, in 2022, prostate cancer is ranked 4th out of 15 cancers that cause the highest deaths in the world. Prostate cancer is formed in the cells of the prostate gland. Most prostate cancers are slow-growing and unlikely to spread, but some can grow faster. The position and dimensions of prostate cancer are visualized with MRI so that treatment methods can be performed with X-ray therapy through LINAC. PHITS is used to simulate X-ray therapy using a voxel or phantom model. The phantom used was an adult American male ORNL phantom. The treatment was simulated using three irradiation directions of 0°, 45°, and 90°. The results stated that to achieve a total dose of 65-70 Gy, 33-35 fractions were required. The more optimal irradiation direction is at 45 degrees, with 1.66 Gy per fraction on the skin and 1.99 Gy per fraction on cancer cells, with a total absorbed dose of 65.8-69.8 Gy.